EXAMINING FACTORS INFLUENCING WHISTLEBLOWING INTENTIONS AMONG ACCOUNTING ALUMNI: THE ROLE OF RELIGIOSITY, PERSONAL COST, WRONGDOER STATUS, ETHICAL EDUCATION AND FRAUD SEVERITY - Faiza Muklis; Andri Novius (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2024)
This research aims to empirically prove the influence of religiosity, personal cost, status of wrongdoer, ethics education, seriousness of fraud, and personal cost which are moderated by reporting channel on whistleblowing intention. The study was conducted on accounting alumni of UIN Sultan Syarif Kasim Riau who were already working. The sampling technique uses a purposive sampling method with a sample size of 100 people. Data analysis uses multiple linear regression analysis. Based on the results of data processing, it shows that the variables religiosity, status of wrongdoer, ethics education, level of seriousness of fraud have effect on whistleblowing intention. Meanwhile, the personal cost and personal cost variables, which are moderated by the reporting channel, have no effect on alumni's intention to carry out whistleblowing. This results shows that religiosity and ethics education can act as behavioral controls in making decisions about whistleblowing. Apart from that, the status of wrongdoer and the level of seriousness of fraud indicate an attitude to avoid fraud occurring and the serious impact of fraudulent acts which have the potential to be detrimental to the institution and the state will increase the intention to carry out whistleblowing.